(untitled) (Revista Argentina de Musicología, 2003)
The presence of melodies in the Phrygian mode in some Argentine folk melodies is demonstrated through comparative analysis. Their main features are studied and typological similarities with medieval European and Spanish popular melodies are detected and described.